Five-member ensemble wave forecast for the R/V Mirai 2023 Arctic Ocean expedition using different sea ice forcing - Nose, Takehiko; Waseda, Takuji; Kodaira, Tsubasa; Xu, Xingkun (2023)
The 14th Symposium on Polar Science/Interdisciplinary sessions [IA] Arctic Research, Thu. 16 Nov. / 2F Auditorium, National Institute of Polar Research conference object